Who's Afraid of Aboriginal Art? - Clark, Jessica Amy (2022)
© 2023 Jessica Amy Clark WHO’S AFRAID OF ABORIGINAL ART? investigated how intercultural curatorial models reframe and redefine narratives and understandings of Aboriginal art. Through a series of three original curated exhibition projects, this practice-led research expanded the framework through which the curation of Aboriginal art has historically been approached and/or confined. Each exhibition brought together diverse Aboriginal and non-Aboriginal Australian visual art practices to generate profound intercultural resonances. Furthermore, each curatorial model was informed by an Indigenous worldview that acknowledges the interconnection and interdependency of life, materiality, and place. Collectively, the exhibitions form the core creative outcomes of this practice-led research and comprise 'one (&) another' (2020–22), 'In and of this place' (2021–22), and 'breathing space' (2021–22). Each exhibition deployed a different intercultural curatorial model for the presentation of Aboriginal and non-Aboriginal Australian art as a means of investigating how Aboriginal art is presented and how Aboriginal artists are represented in the broader context of Australian art. This was achieved through a visual and spatial levelling of artworld hierarchies (such as those that are identity-based, geographic, and/or medium-specific) that have historically informed the selection and display of Aboriginal art. For the purposes of this practice-led research, this exegesis presents each exhibition outcome within a respective chapter – “Chapter 1: one (&) another”, “Chapter 2: In and of this place”, and “Chapter 3: breathing space”. While the exegesis presents the exhibitions sequentially, they evolved concurrently. “Chapter 1: one (&) another” presents a dual-format exhibition featuring two distinct bodies of work: a collection of brightly coloured fibre baskets by Tjanpi Desert Weavers (Aboriginal) and a series of video works by Taree Mackenzie (non-Aboriginal). By bringing Tjanpi baskets together with Mackenzie’s ...